Plasma exchange in systemic lupus erythematosus. - Parry, H F (1981)
Eight out of 10 patients studied longitudinally received benefit from plasmapheresis. The patients were used as their own controls, being treated in a steady state as far as was possible. Levels of circulating complexes did not bear a close relationship with clinical results. On the evidence plasma exchange alone does not appear to represent an important part of the long-term management of patients with systemic lupus erythematosus but may well be of value in combination with other therapy.